PENGARUH DRILL MENGGIRING BOLA TERHADAP KEMAMPUAN DRIBBLING PADA SEKOLAH SEPAK BOLA MERAH PUTIH U-15 BANGKINANG - Wawan Setiawan; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The aim of this study was to find out how much influence the Dribbling Drill had on dribbling skills at the U-15 Bangkinang Red and White Football School. This research was conducted at the U-15 Red and White SSB field in Bangkinang, similarly at Tuanku Tambusai Bangkinang Station, from 12 October 2021 to 12 February 2022. In this study, researchers used a one group pretest-posttest design. pre-test and post-test before and after being given treatment. Prior to the analysis, a pre-test was carried out on athletes with an average of 22.10, then short training was carried out for 16 meetings at the U-15 Red and White Football School Bangkinang, totaling 16 people and the average post -test of 19.12. Based on the analysis of pretest and posttest data, there was an average increase of 2.98 and resulted in a Thitumg of 12.41 and a Ttable of 1.753. Based on the data analysis and discussion, it can be concluded that there is an influence of dribbling drills on dribbling abilities at the Bangkinang U-15 Football School as evidenced by Tcount 12.41 > Ttable 1.764 at α = 0.05.Key Words; Drill Dribble, Dribbling Ability